THE ANALYSIS THE EFFICIENCY OF THE INDONESIAN FAMILY HOPE PROGRAM IN ACEH PROVINCE: DEA ANALYSIS APPROACH - safwan nurdin; Irfan Irfan; Marzuki Marzuki (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study measures the relative efficiency of the conditional cash transfer of the Indonesian Family Hope Program (PKH) in 23 districts / cities in Aceh Province during the period 2015 to 2021 by using two input variables, namely Budget Allocation and PKH Facilitators (PKH HR) and one output variable, namely PKH Beneficiary Families (KPM). This study uses the Data Envelopment Analysis (DEA) analysis tool with the output-oriented Variable Return to Scale (VRS) model approach. relative efficiency using a non-parametric approach. The results showed that the annual average efficiency level of the PKH Program during the period was 0.867 or 13.3% inefficiency. There were 10 regions with efficiency levels above average efficiency and 13 districts/cities below average efficiency. The highest is Singkil Regency with an efficiency level of 0.947 and the lowest is Simeulu Regency at 0.806. Efficiency measurements need to be carried out continuously to identify which PKH programs in which regions are inefficient in providing better social protection both in terms of budget allocation and absorption, assistance, and protection for beneficiary families (KPM). So that information on the efficiency of each region is needed as material for evaluation and improvement where inefficient areas need strategic efforts so that the level of efficiency towards optimal is improved while the area has a good level of efficiency can maintain and maintain it so that the objectives of the family hope program according to its guidelines can be realized.